Hop on Pop - Dr. Seuss Dr. (New York : Beginner Books, 1963)
Pairs of rhyming words are introduced and used in simple sentences, such as "Day. Play. We play all day. Night. Fight. We fight all night."
Keywords: Stories in rhyme